Motor imagery promising technique for Rehabilitation of Patients with Parkinson's disease: A Systematic Review - Kashif, Muhammad; Ahmad, Ashfaq; Bashir, Kiran; Farooq, Maryam; Maqbool, Saba; Nadeem, Iqra (Journal of Liaquat University of Medical & Health Sciences, 2023)
Recent research has suggested that motor imagery may be helpful for the Rehabilitation of Parkinson's disease (PD) patients. Using MI, a movement can be imagined without muscles being activated. MI induces plastic changes in the motor cortex, improving motor performance. This systematic review was designed to examine the effects of MI on the physical rehabilitation of people with Parkinson's disease. Five databases were used to identify similar studies using selected keywords. This review assessed the "methodological quality of each randomized control trial study" using the eleven-point Physiotherapy Evidence Database scale, widely used to rate physiotherapy "literature". The benefits of using MI to treat patients with PD were identified in this review. Seven studies were identified; 6 studies reported motor function, two studies worked on bradykinesia, two on balance and two reported impairments in Gait in PD using MI. The included studies had small samples, varied methodological approaches, and varied quality from good to fair. According to the current review, MI provides more significant benefits for Parkinson's patients than conventional physical therapy alone when used along with other therapeutic methods for improving motor function and balance. Keywords: Rehabilitation, Parkinson's disease, Motor imagery, systematic review